Peran Kolaborasi Guru dan Orang Tua dalam Pembentukan Karakter Siswa Sekolah Dasar - Wanda Gridelvia Saamad; Berlyana Amanda Charisma Putri; Elsa Ramadani; Dita Rima Oktaviana Oktaviana; Aulia Cahya Ramadhani; Herlina Herlina; Kadek Hariana (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2024)
Character building is one of the important aspects in shaping the next generation of the nation that is not only smart but also has good character. Therefore, the importance of collaboration between teachers and parents in the character building of elementary school students. The objectives of this study are to (1) identify the forms of effective collaboration between teachers and parents in character building of elementary school students, (2) analyze the factors that influence the success of collaboration between teachers and parents in character building of elementary school students, and (3) explore the positive impacts resulting from collaboration between teachers and parents in character building of elementary school students. The method used in this research is Systematic Literature Review (SLR) with a meta-synthesis approach. The literature reviewed in this article amounted to 15 articles obtained from Google Scholar with publication vulnerability between 2016 and 2024. The results of this study show that the forms of collaboration include structured communication, active involvement of parents in school programs, strengthening moral values through joint activities, and synergy in cultivating religious character. The success of this collaboration is influenced by several factors, namely commitment and awareness from teachers and parents, quality communication between teachers and parents, curriculum standards and school policies, exemplary teachers and parents, and the influence of the social environment and technology. In addition, the strengthening of character values, psychological well-being, social skills, and adaptation to modern challenges are positive impacts resulting from this collaboration.